The effect of board equity ownership towards the relationships between corporate governance, corporate social responsibility, and company’s performance of oil palm companies in Indonesia - , Asna (2022)
For the last few decades, the Indonesian Oil Palm industry has contributed to economic development by reflecting on the percentage contribution to the Gross Domestic Product. However, most of those companies had a history of poor financial performance. Poor performance has been linked to inefficient corporate governance mechanisms, corporate social responsibility, and board equity ownership. Thus, this study aimed to examine the effects of corporate governance mechanisms, corporate social responsibility, and the moderation effect of board ownership equity between the specified linkages. A quantitative research design approach was chosen, with a questionnaire developed for primary data collection via a survey of 281 Indonesian oil palm companies’ board of directors from three regions using the stratified random sampling technique. The partial least square regression was applied to analyze the relationship between the variables. The findings show that the dimension of corporate governance, such as independent director, female director, and board process, has significant positive effects on company performance. Likewise, environmental responsibility and community responsibility as dimensions of corporate social responsibility significantly positively affect company performance. Based on the results of the moderation effects, board ownership equity strengthens the relationship between corporate governance, corporate social responsibility, and company performance. The findings have several implications for the company’s owner, including raising awareness among family businesses about the importance of an independent director as a board member, re-evaluating the size of the board, expanding the list of corporate social responsibility activities that are tax-deductible, creating a solid risk management policy, and encouraging companies to allow board members to have at least 5% of the total company share, as recommended in the Law No. 40 of 2007 on the Regulation of Limited Liability Companies.